The Influence Of Dietary Energy, Protein And Copper Levels On The Sulphur Amino Acid Requirements Of Broiler Chickens - Suwanpradit, Somchai (1994)

(untitled)
Three experiments were conducted with male broiler chicks to determine the influence of dietary metabolisable energy ( ME ) , crude protein (CP) and copper (Cu ) levels on the total sulphur amino acid (TSAA) requirement of broilers both during the starter ( 0-3 wk) and t he grower periods ( 4-6 wk) reared in the tropics . In all the experiments the parameters used to evaluate the TSAA requirements are body weight gain , feed : gain ratio and carcass composition. In the first experiment , two factorial arrangements of three ME levels ( 3000 , 3200 and 3400 kcal /kg ) x four level sof TSAA ( 0 . 73 , 0 . 83 , 0 . 93 and 1. 03% ) and the same three ME levels ( 3000 , 3200 and 3400 kcal /kg ) x four levels of TSAA ( 0 . 65 , 0.72 ,0.79 and 0.86% ) were used for t he starter and the grower periods,respectively . The results showed significant differences ( p< . 05 ) in body weight gain and feed : gain ratio of the broilers within creasing dietary TSAA levels both in starter and grower periods. There were no significant interaction ( p< . 05 ) between dietary ME and TSAA levels for the performance , with the exception for feed in take of starter broilers . It indicated that for the starter period , a TSAA of 0 . 93% produced the best performance regardless of energy levels while for the grower period the requirement of TSAA at both 0 . 79 and 0 . 86% were suggested . The results further showed that dietary energy levels had no effect on the TS AA requirement of the broilers.